EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF MURDER RME DAN MURDER PADA MATERI STATISTIKA DITINJAU DARI KEMANDIRIAN BELAJAR MATEMATIKA SISWA KELAS XI SMA - Widyana Wahyuningtyas; Mardiyana Mardiyana; Sri Subanti (Journal of Mathematics and Mathematics Education, 2016)
Abstract: The aim of the research was to determine the effect of learning models on mathematics achievement viewed from the student self-regulated learning. The learning models compared were MURDER (Mood Understand Recall Detect Elaborate Review) using RME (Realistic Mathematics Education) approach, MURDER, and direct learning. This study was a quasi-experimental research. The population of this study was students in grade XI science of Senior High School in Ponorogo on academic year 2015/2016. Instruments used were mathematics achievement test and questionnaire. Two ways anova with 3x3 of factorial design and significance level 0,05 are used for hypothesis test. The conclusions of the research were as follows. (1) MURDER RME gives better achievement than MURDER and direct learning, and MURDER gives the same achievement as direct learning, (2) students with high self-regulated learning has the same achievement as those who has middle self-regulated learning. Students who have high and middle self-regulated learning have better achievement than low self-regulated learning, (3) in the MURDER RME and MURDER, students who have high, middle, and low self-regulated learning have the same achievement. In the direct learning, students who have high self-regulated learning have the same achievement as those who have high and low self-regulated learning, and students who have high self-regulated learning have better achievement than those students who have low self-regulated learning, (4) for high self-regulated learning, MURDER RME produces better achievement than MURDER; MURDER RME and MURDER produce the same achievement as direct learning. For middle and lowself-regulated learning, MURDER RME, MURDER, and direct learning produce the same achievement which is categorized as good.Keywords: MURDER, RME, Self-Regulated Learning